TINJAUAN YURIDIS UPAYA PENGEMBALIAN KERUGIAN NEGARA MELALUI PENJATUHAN PIDANA TAMBAHAN BERUPA UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI DIKAITKAN DENGAN NILAI KERUGIAN NEGARA YANG DITIMBULKAN - Weldy Marlius; Dessy Artina; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Corruption is a familiar problem in the ears of the Indonesian people. Corruption causes a huge impact on state financial losses and impedes national development. The main purpose of the Law on combating corruption is to restore state losses. However, in practice, efforts to recover state losses have not been effective.The purpose of writing this thesis, namely: First, To find out how efforts to recover the losses of the State through additional criminal money substitute in criminal acts of corruption. Second, to find out how the ideal criminal concept is additional replacement money to recover state losses due to corruption.In this study the authors used a type of normative legal research. Normative legal research is legal research by conducting a study of existing materials. This study uses secondary data that is library data related to the object of research by conducting library research. Analysts used in this research use qualitative analysis.From the results of this study it can be concluded that, First In practice many cases are able to be proven by the public prosecutor in a criminal court of corruption but the return of state losses which is the goal of the Law on the Eradication of corruption itself is still far from expectations. Secondly, law enforcement against corruptors should be renewed, considering that up to now the law enforcers are still having difficulty in returning state losses caused by corruption.Keywords: Corruption-Returns State Losses